PEMETAAN SEBARAN PARTIKULAT DARI PEMBAKARAN LIMBAH PADAT INDUSTRI PENGOLAHAN SAWIT, DI KABUPATEN KAMPAR, RIAU - Aryo Sasmita; David Andrio; Parlaung Hasibuan (Jurnal Sains dan Teknologi, 2019)
The use of boilers and incinerators in the palm oil processing industry will contribute to pollutants in the form ofparticulates (PM2.5 and PM10) which are quite large in number. Particulates are pollutants that have a high level oftoxicity that can endanger human health and the surrounding environment. This study aims to determine the amount ofpollutants resulted from palm oil mills as well as mapping the distribution patterns in the environment. To be able todescribe the pattern of pollutant spread, it starts by identifying the factors that influence the spread of pollutants suchas the amount of pollutants produced, atmospheric stability, wind direction and speed. These data were obtained fromthe Meteorology and Geophysics Agency of Pekanbaru City. To describe the spread of particulate pollutants, asimulation model is used which has been integrated into the AERMod software. The results of the study show that thedirection of the distribution of emissions for pollutants PM2.5 and PM10 from the simulation model results tend towardsoutheast and north from the source. The highest PM2.5 concentration value for the 24-hour was 9.26 µg / m3, thehighest for 1 year was 1.48 µg / m3. The highest value of PM10 concentration for 24 hours is 18.23 µg / m3, the highestfor 1 year is 2.87 µg / m3. The simulation results show that the concentration of pollutants PM2.5 and PM10 originatingfrom boilers and incinerators are below the quality standards of each pollutant.